Consumer behavior and healthy eating: implications for social marketing - Serikbayeva, A. (International School of Economics KAZGUU, Nur-Sultan, 2022)
Effective interventions towards changing eating habits depend on understanding of the factors that influence to choose certain behavior. We need to understand why people prefer to eat the way they eat. So, it is important to investigate the role of motives affecting on selection of food. This research aims to investigate the food motives of population in Kazakhstan in relation to socio-demographic factors (gender, age, gross income, and work hours). We examined food motives of population in Kazakhstan, their role in relation to proper nutrition. The study has improved our understanding of consumer behavior in relation to nutrition, their motives and motivation. This research paper can be useful in developing social marketing strategies to improve nutrition and influence food choices. Quantitative data from a total of 91 respondents were used. The research shows that gender and work hours influence eating motives. Social marketing interventions based on age and gross income potentially will be effective in other countries and did not effective in Kazakhstan. Social marketing intervention campaigns based on gender and work hours regarding healthy eating will be effective social marketing strategy. The structure and volume of the dissertation: The dissertation consists of an introduction, literature review, methodology, findings, conclusion, limitations, references, and annex
Keywords: social marketing, healthy eating, food motives, consumer behavior